Challenges encountered by teachers when teaching fractions in Grade 2 at Koloti Circuit : Capricorn District, Limpopo Province - Masenya, Mmapula Nelly (My University, 2021)
The purpose of the research was to explore challenges encountered by teachers when teaching fractions to learners in grade 2 at schools in the Koloti Circuit. A qualitative approach including other research techniques, such as observation, document analysis and interviews, were mutually employed to collect data during the study. A pluralistic approach was employed when gathering data to enhance triangulation and further intensify the merits of the probed facts. Purposive sampling was employed to choose three grade 2 teachers from various schools to serve as participants in this study. The following challenges were uncovered as a result of the research: learners are from child-headed families; there is a high rate of learner absenteeism; parents do not attend consultative meetings; there is a high rate of teacher time-offs; there is a lack of teacher pedagogical content knowledge in mathematics; teachers have to teach in multi-grade classroom; teachers lacking background knowledge on implementation of inclusive classrooms resulting in inadequate support to learners with learning barriers; classrooms are over-crowded; uneven partitioning of circular representations was discovered, and there is lack of content-related workshops. The following were some of the recommendations that were established to counteract the challenges uncovered during the research study, namely: establishment of after-care centres with qualified tutors; provision of state paid security services in schools; teachers should create learner support materials to aid in the teaching of fractions to the learners; teachers should notify parents when their children are absenting themselves from school on regular basis without valid reasons; teachers should notify parents about the benefits of attending consultative meetings; memorial services for teachers should be conducted after learner contact time, competent and/or qualified teachers in arithmetic should be assigned to educate the subject; small schools should be merged to curb multi-grate teaching at schools; more classrooms should be provided to avoid over-crowding in the classrooms, and more content workshops should be organised in order to assist teachers who experience challenges with the teaching of fractions. In conclusion, the outcomes of this study could aid grade 2 teachers in instilling knowledge of fractions into their learners, crafted on the suggested recommendations that are drawn subsequent the challenges facing teachers were singled out, in order to improve learner performance in fractions. This could result in better performance by learners in mathematics at various schools.
Thesis (M. Ed. (Curriculum Studies)) -- University of Limpopo, 2021
Keywords: Mathematics; Fraction; Foundation phase; Learners; Teachers; Teacher content knowledge; contextual knowledge; teaching approaches; Mathematics -- Study and teaching (Elementary); Fractions; Education -- Teaching materials and methods; Fractions -- study and teaching (Elementary)